URGENSI REFORMASI UNDANG-UNDANG TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN SEBAGAI DAMPAK PENERAPAN KONSEP OMNIBUS LAW DI INDONESIA - Achmad Jaka Santos Adiwijaya; Danu Suryani; Kukuh Komandoko; Muhammad Vijay (JURNAL ILMIAH LIVING LAW, 2022)
The purpose of this study is to identify and analyze the need for regulatory reform regarding the formation of laws and regulations to organize legislation in Indonesia and what effect the Omnibus Law method has in the formation of laws and regulations in Indonesia. The method used in this study is normative juridical, with data collection carried out by analyzing data obtained in laws and regulations, books, journals, research results, observation methods, and interview methods. This study concludes that Law Number 12 of 2011 concerning the Establishment of Legislation and its amendments has not accommodated the legislation drafting technique using the Omnibus Law method. The opportunities for further use of the Omnibus Law method are First, with the adoption of the Omnibus Law in the formation of legislation through Law Number 11 of 2020 concerning Job Creation, the government needs to follow up by reforming the Law on the Establishment of legislation. Second, the government needs to examine the implementation of the laws formed using the Omnibus Law method.